Perbaikan Kesehatan Lingkungan Dengan Pendekatan Sanitasi Total Berbasis Masyarakat Di Kabupaten Ogan Komering Ulu Sumatera Selatan - Enda Kartikasari; Lindawati Lindawati (Abdimas Universal, 2019)
The objectives of the program include: a) Building a public toilet that is representative of the community as an effort to implement the Community-Based Total Sanitation village in Tanjung Pura Village, Pengandonan Kabipaten Sub-District, Ogan Komering Ulu. b) Obtain program recommendations that involve community participation in hygiene behavior and form a community-based total sanitation village in Tanjung Pura Village, Pengandonan Sub-District, Ogan Komering Ulu Regency. As for behavior changes that occur after assistance, the behavior of treating waste Reduce, Reuse and Recyle garbage has been carried out by the community for 30 percent. Reprocessing (recycling) waste into a useful product 30 percent has been done by the community. the mentoring steps carried out as an effort to improve hiegiene behavior and build a community-based total sanitation village gave quite good results. Changes in behavior that have occurred in the community have begun to become apparent, such as changes in not disposing of garbage and defecating in rivers (STOP BABS in rivers). Changes occur at 50 percent. The community no longer disposes of garbage and defecates in the river and the location on the edge of the river has started to clear from garbage. The availability of public toilets for the community is very helpful in implementing the program. Changes that occur in the community after the provision of this public toilet is quite good. 40 percent of the people in Tanjung Pura Village, OKU Regency, have started using public toilets for BAB activities. Keywords: Environmental Health, Community Based Total Sanitation